Effect of phase-shift feedback on thermoacoustic coupling. Issue 10 (2016) - Morán, Beatriz M.; Saurabh, A.; Paschereit, C.O.; Kabiraj, L.
Abstract: In the present investigation we report our experiments dealing with the effect of phase-shift feedback on chaotic thermoacoustic oscillations in a premixed flame Rijke burner—a fundamental configuration employed frequently in the study of thermoacoustic coupling, which is currently a pressing problem in engineering systems such as gas turbine combustors, furnaces and rocket engine combustors. The phenomenon of thermoacoustic coupling itself is yet another nonlinear feedback coupling phenomenon, which has only very recently been identified exhibit a wide spectrum of complex dynamics, including chaos. The ultimate aim of research in this field is to control thermoacoustic oscillations. That thermoacoustic coupling can exist as chaos and other nonlinear states has implications on existing control strategies. We show here that the commonly employed phase-shift control results in an additional complexity, and that the resulting state could correspond to different nonlinear oscillations depending on the phase-shift feedback parameters.